Differences in Sequential Eye Movement Behavior between Taiwanese and American Viewers - Lee, Yen-Ju; Greene, Harold H.; Tsai, Chia W.; Chou, Yu J. (Frontiers in Psychology, 2016)
Knowledge of how information is sought in the visual world is useful for predicting and simulating human behavior. Taiwanese participants and American participants were instructed to judge the facial expression of a focal face that was flanked horizontally by other faces while their eye movements were monitored. The Taiwanese participants distributed their eye fixations more widely than American participants, started to look away from the focal face earlier than American participants, and spent a higher percentage of time looking at the flanking faces. Eye movement transition matrices also provided evidence that Taiwanese participants continually, and systematically shifted gaze between focal and flanking faces. Eye movement patterns were less systematic and less prevalent in American participants. This suggests that both cultures utilized different attention allocation strategies. The results highlight the importance of determining sequential eye movement statistics in cross-cultural research on the utilization of visual context.